Survival of corticostriatal neurons by Rho/Rho-kinase signaling pathway. (6th September 2016) - Kobayashi, Kenta; Sano, Hiromi; Kato, Shigeki; Kuroda, Keisuke; Nakamuta, Shinichi; Isa, Tadashi; Nambu, Atsushi; Kaibuchi, Kozo; Kobayashi, Kazuto
Highlights: A novel conditional genetic approach using a dual viral vector system was applied. C3 transferase or Rho-K DN was conditionally expressed in corticostriatal neurons. Inhibition of Rho/Rho-kinase signaling caused corticostriatal neuron apoptosis. Abstract: Developing cortical neurons undergo a number of sequential developmental events including neuronal survival/apoptosis, and the molecular mechanism underlying each characteristic process has been studied in detail. However, the survival pathway of cortical neurons at mature stages remains largely uninvestigated. We herein focused on mature corticostriatal neurons because of their important roles in various higher brain functions and the spectrum of neurological and neuropsychiatric disorders. The small GTPase Rho is known to control diverse and essential cellular functions through some effector molecules, including Rho-kinase, during neural development. In the present study, we investigated the role of Rho signaling through Rho-kinase in the survival of corticostriatal neurons. We performed the conditional expression of Clostridium botulinum C3 ADP-ribosyltransferase (C3 transferase) or dominant-negative form for Rho-kinase (Rho-K DN), a well-known inhibitor of Rho or Rho-kinase, respectively, in corticostriatal neurons using a dual viral vector approach combining a neuron-specific retrograde gene transfer lentiviral vector and an adeno-associated virus vector. C3 transferase markedly decreased the number of corticostriatal neurons, which was attributed to caspase-3-dependent enhanced apoptosis. In addition, Rho-K DN produced phenotypic defects similar to those caused by C3 transferase. These results indicate that the Rho/Rho-kinase signaling pathway plays a crucial role in the survival of corticostriatal neurons.